Structure and morphology of CrSi2 layers formed by rapid thermal treatment - J. A. Solovjov; V. A. Pillipenko; P. I. Gaiduk (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2020)
The formation of chromium disilicide layers on n-type single crystal silicon substrates (111) during rapid thermal annealing in heat balance mode by the methods of Rutherford backscattering, X-ray diffraction and transmission electron microscopy of cross sections was investigated. Chromium films of about 30 nm thickness were deposited by magnetron sputtering of a chromium target with argon ions onto silicon substrates at room temperature. The rapid thermal treatment was carried out in a temperature range of 200 to 550 °C in a heat balance mode by irradiating the substrates backside with a non-coherent light flux of quartz halogen lamps in a nitrogen ambient for 7 s. It was established that hexagonal phase of chromium disilicide formation with grain size of 150–300 nm occurs in a threshold manner when the temperature of rapid thermal treatment exceeds 400 °C. At the same time, there are strong changes in the films surface morphology and surface roughness, and a silicide-silicon interface occur. In this case the wavy film surface morphology practically repeats silicide-silicon interface morphology (the surface exactly replicates the interface). The mechanism of CrSi2/Si interface structure roughness formation based on consideration of Kirkendall effect and deformation-stimulated diffusion of vacancies is proposed and discussed. The research results of the structure and morphology of CrSi2 layers on silicon are well-correlated with the results of the Schottky barrier electrophysical measurements. The results obtained can be used in microelectronics for forming rectifying contacts and interconnects metallization for integrated circuits, as well as for thermoelectric and optoelectronic applications.